Coaching without a compass: Why the Philippines needs a national framework for coaching education - Balore, Julibert Jr Noynoyan; Suniga, John Paul C.; Jurek, Joanna Michalina (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Coaches play a critical role in athlete development, yet coaching education in the Philippines remains fragmented, decentralized, and under-regulated. Despite the growing success of Filipino athletes on the international stage, the absence of a national framework has resulted in inconsistent certification standards, limited access to continuing professional development (CPD), and uneven opportunities for career progression. This study aims to address this gap by proposing a unified National Coaching Education Framework (NCEF) for the Philippines. Material and Methods. The study employed a policy-oriented approach that combined a structured literature review with comparative policy analysis of international models such as Canada"™s National Coaching Certification Program (NCCP), the United Kingdom"™s Coaching Certificate (UKCC), and Singapore"™s Continuing Coach Education (CCE) Program. Thematic analysis was conducted across academic literature, government reports, and institutional documents. Results. Findings reveal four critical issues: (1) fragmentation and lack of standardization in certification, (2) limited access to CPD, (3) inequities in affordability and regional accessibility, and (4) a disconnect between academic preparation and applied coaching practice. Based on these insights, the proposed NCEF introduces a tiered certification system"”community, developmental, and elite/high-performance coaches"”supported by mandatory CPD, ethics, and safeguarding standards. Conclusions. This framework contributes to the professionalization of coaching in the Philippines while aligning with international benchmarks. It also provides practical implications for policymakers and institutions, offering a pathway toward a more equitable, accountable, and sustainable coaching system.